Work Environment and Workload on Job Satisfaction with Job Stress as an Intervening Variable on Situbondo Regency Government Employees - Sofi, Aida Hikmatus; Herlambang, Toni; Sanosra, Abadi (Jurnal Ilmu Manajemen Advantage, 2024)
A survey on job satisfaction among local government employees in Situbondo Regency revealed concerns about limited promotion opportunities and lack of involvement in the promotion process for some workers. Job satisfaction is influenced by various interconnected factors, including work environment, workload, and job stress. This study aimed to examine the direct and indirect effects of work environment and workload on job satisfaction, with job stress as an intervening variable, in the Situbondo Regency Government. The total population who became respondents in this study were 61 respondents. Since this figure represents the complete research sample, saturation sampling (census) is the sampling strategy used and employed structural equation modeling (SEM). Results indicated that both work environment and workload significantly impacted job stress and job satisfaction. However, job stress was not found to have a significant effect on job satisfaction. Additionally, the study concluded that work environment and workload, when mediated by job stress, did not significantly influence job satisfaction.